Association between cytokines and psychiatric symptoms in chronic fatigue syndrome and healthy controls. (17th November 2018) - Groven, Nina; Fors, Egil A.; Iversen, Valentina C.; White, Linda R.; Reitan, Solveig Klæbo
Abstract: Purpose: The reports regarding the status of the immune system in patients with chronic fatigue syndrome/myalgic encephalopathy (CFS/ME) have been inconclusive. We approached this question by comparing a strictly defined group of CFS/ME outpatients to healthy control individuals, and thereafter studied cytokines in subgroups with various psychiatric symptoms. Materials and methods: Twenty patients diagnosed with CFS/ME according to the Fukuda criteria and 20 age- and sex-matched healthy controls were enrolled in the study. Plasma was analysed by ELISA for levels of the cytokines TNF-α, IL-4, IL-6 and IL-10. Participants also answered questionnaires regarding health in general, and psychiatric symptoms in detail. Results: Increased plasma levels of TNF-α in CFS/ME patients almost reached significance compared to healthy controls ( p  = .056). When studying the CFS/ME and control groups separately, there was a significant correlation between TNF-α and The Hospital Anxiety and Depression Scale (HADS) depressive symptoms in controls only, not in the CFS/ME group. A correlation between IL-10 and psychoticism was found in both groups, whereas the correlation for somatisation was seen only in the CFS/ME group. When looking at the total population, there was a significant correlation between TNF-α and both the HADS depressive symptoms and the SCL-90-R cluster somatisation. Also, there was a significant association between IL-10 and the SCL-90-R cluster somatisation when analyzing the cohort (patients and controls together). Conclusions: These findings indicate that immune activity in CFS/ME patients deviates from that of healthy controls, which implies potential pathogenic mechanisms and possible therapeutic approaches to CFS/ME. More comprehensive studies should be carried out on defined CFS/ME subgroups.